Identity, place, and subversion in contemporary Mizrahi cinema in Israel - Shemer, Yaron (University of Michigan Press, 2013)
In this book, the author articulates the modalities through which Mizrahi (Eastern-Jewish or Arab-Jewish) films employ narratives, characters, and space to glean ethnic identities and, often, to redraw ethnic boundaries. This study's approach to Mizrahi ethnicity in Israel then stands in stark contrast to the conventional precept of the societal pastiche in modern Israel and the regnant discourse about the widespread dismissal of ethnic divisions in the country. For decades after the establishment of the State, Israeli films mostly acquiesced with Zionism's dominant discourse whereby the Mizrahi was deemed an inferior other whose "Levantine" culture was believed to pose a threat to the Western-oriented Zionist enterprise. The author explores the continuous marginalization of the Mizrahi in contemporary Israeli cinema and the challenge some Mizrahi films offer to the subjugation of this ethnic group. Beyond its textual analysis, the book examines the role cultural policies and institutional power in Israel have played in shaping Mizrahi cinema and the creation of a Mizrahi niche in cinema - a space that defines and contains contesting voices more than it nourishes them. This work is designed to facilitate the making of "Mizrahi Cinema" as a legitimate, recognized, and vibrant scholarly field. --